A community pharmacist‐led anticoagulation management service: attitudes towards a new collaborative model of care in New Zealand. (24th February 2014) - Shaw, John; Harrison, Jeff; Harrison, Jenny
Abstract Objective To examine attitudes towards a new collaborative pharmacy‐based model of care for management of warfarin treatment in the community. As background to the study, the New Zealand health authorities are encouraging greater clinical involvement of community pharmacists. Methods Fifteen community pharmacies in New Zealand took part in a community pharmacist‐led anticoagulation management service (CPAMS). Participants (patients, general practitioners, practice nurses, pharmacists) were surveyed on their views on accessibility, convenience, confidence in the service, impact on warfarin control, impact on workloads, effect on relationships and whether the service should be further implemented. A small number from each group was interviewed on the same topics. Key findings Patients reported improved access, convenience, a preference for capillary testing, and the immediacy of the test result and dose changes. They indicated that they had a better understanding of their health problems. While sample sizes were small, the majority of general practitioners and practice nurses felt there were positive benefits for patients (convenience) and themselves (time saved) and expressed confidence in pharmacists' ability to provide the service. There were some concerns about potential loss of involvement in patient management. Pharmacists reported high levels of satisfaction with better use of their clinical knowledge in direct patient care and that their relationships with both patients and health professionals had improved. Conclusions The new model of care was highly valued by patients and supported by primary care practitioners. Wider implementation of CPAMS was strongly supported. Pharmacists and general practitioners involved in CPAMS reported a pre‐existing collaborative relationship, and this appears to be important in effective implementation.